2015
DOI: 10.1002/jmri.25053
|View full text |Cite
|
Sign up to set email alerts
|

Incidental extracardiac findings on cardiac MR: Systematic review and meta-analysis

Abstract: Major IEFs may be found in 12% of patients undergoing cardiac MR examination and change the management in 1% of patients. Readers' training for the evaluation of noncardiac structures increases reported prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…We included 20 systematic reviews from 7098 references identified from our database search (fig 1). 7 8 9 28 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 These 20 systematic reviews included 240 primary studies and 627 073 patients. Fifteen systematic reviews provided data to quantify the prevalence of detecting incidentalomas7 8 9 28 30 31 32 33 34 35 36 37 38 39 45 (table 1), whereas 18 provided data to quantify the outcomes of incidentalomas7 8 9 28 30 31 32 33 34 35 38 39 40 41 42 43 44 45 (table 2) (13 provided both).…”
Section: Resultsmentioning
confidence: 99%
“…We included 20 systematic reviews from 7098 references identified from our database search (fig 1). 7 8 9 28 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 These 20 systematic reviews included 240 primary studies and 627 073 patients. Fifteen systematic reviews provided data to quantify the prevalence of detecting incidentalomas7 8 9 28 30 31 32 33 34 35 36 37 38 39 45 (table 1), whereas 18 provided data to quantify the outcomes of incidentalomas7 8 9 28 30 31 32 33 34 35 38 39 40 41 42 43 44 45 (table 2) (13 provided both).…”
Section: Resultsmentioning
confidence: 99%
“…Sohns et al [ 10 ] reported in 234 cMRI studies a slightly higher rate of extracardiac findings (26% of 854 patients), almost comparable with the prevalence in Irwin et al's work [ 9 ] (21.4% of 714 patients). A recent systematic review and meta-analysis of 12 studies including data from 7,062 patients demonstrated pooled prevalence of incidental extracardiac findings of 35% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians and researchers should therefore anticipate incidental findings and develop appropriate policies for managing them, taking into account their expected prevalence and clinical severity. 7 Existing data on the prevalence of incidental findings from systematic reviews of MRI of one body region, 8 patient populations undergoing MRI, 9 or apparently asymptomatic people imaged by another modality, 10 are not generalisable to brain and body MRI of apparently asymptomatic people. Here, asymptomatic people are defined as community dwelling individuals not selected for imaging on the basis of symptoms, risk factors, or disease.…”
Section: Introductionmentioning
confidence: 99%